2018
DOI: 10.1590/1806-9061-2018-0787
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Dietary Supplementation with Tributyrin and Coated Sodium Butyrate on Intestinal Morphology, Disaccharidase Activity and Intramuscular Fat of Lipopolysaccharide-Challenged Broilers

Abstract: The objectives of this study were to investigate the effects of tributyrin (TB) and coated sodium butyrate (CSB) on intestinal morphology, disaccharidase activity and intramuscular fat of broilers challenged with lipopolysaccharide (LPS). A total of 160 1-day-old healthy Cobb broilers were randomly allocated into four groups: (1) control; (2) LPS, in which broilers were fed a basal diet and intraperitoneally injected with 500 μg/kg LPS on days 38, 40 and 42; (3) TB, in which LPSchallenged broilers were fed bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 36 publications
2
12
0
Order By: Relevance
“…acetate and butyrate in JM might positively contribute to the intramuscular adipogenesis in mouse recipients. Some researchers have reported that dietary supplementation of butyrate can prevent diet-induced insulin resistance and obesity by promoting energy expenditure and induce mitochondria function (46,47) and can decrease IMF content in mice and Broilers (30,48). Here we found a remarkable decrease of colonically derived butyrate in JM compared with that in LM, which might contribute to the higher IMF content in JM.…”
Section: Discussionsupporting
confidence: 54%
“…acetate and butyrate in JM might positively contribute to the intramuscular adipogenesis in mouse recipients. Some researchers have reported that dietary supplementation of butyrate can prevent diet-induced insulin resistance and obesity by promoting energy expenditure and induce mitochondria function (46,47) and can decrease IMF content in mice and Broilers (30,48). Here we found a remarkable decrease of colonically derived butyrate in JM compared with that in LM, which might contribute to the higher IMF content in JM.…”
Section: Discussionsupporting
confidence: 54%
“…Nazih et al [43] demonstrated that butyrate was the only fatty acid that significantly increased the synthesis and the secretion of ApoA-IV protein, which is a major component of HDL and promotes the synthesis of ApoA-IV-containing HDL [44]. Xiong et al [45] showed that tributyrin supplementation in LPS-challenged broilers increased serum HDL compared to LPS-challenged broilers without any feed supplement. Our study, together with previous results, showed that tributyrin might lead to positive effects on blood lipid regulation.…”
Section: Discussionmentioning
confidence: 99%
“…Sodium butyrate is a common additive in diets of poultry and livestock. It has been shown to promote intestinal development, regulate immune response, increase nutrient absorption and ameliorate intestinal environment (Hu & Guo, 2007;Kotunia et al, 2004;Liu, Yang et al, 2014). The improved effects on intestinal villi by sodium butyrate feeding have been widely reported in several fish, including tilapia , seabass (Wassef et al, 2019), Arapaima gigas (Luz et al, 2019) and grass carp (Liu et al, 2017;Tian et al, 2017;Zhou et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…after fed sodium butyrate, the pH and isobutyric acid concentration in caecum of weanling pigs are increased (Biagi et al, 2007). Other studies show that sodium butyrate supplementation promotes feed conversion ratio in chicken (Hu & Guo, 2007) and calves (Guilloteau et al, 2009). The immune activities are also regulated by feeding with sodium butyrate supplementation (Huuskonen et al, 2004;Liu, Yang et al, 2014;Zhang et al, 2011).…”
mentioning
confidence: 97%